Travel and the Pan African Imagination - Flemming, Tracy Keith (Black Diasporic Worlds: Origins and Evolutions from New World Slaving Series, 2021)
This book explores the African Atlantic world as a productive theater or space where modernity, racialized dominance, and racialized resistance took form. The book examines Black Power ideology, Pan Africanism, dilemmas facing the racialized imagination of African world community figures, and the discipline of Africology.